(untitled) (Forum Penelitian Agro Ekonomi, 2016)
Human Development Index (HDI) on development trend during 1980-2012 in Indonesia improved, but food insecurity is still frequently found and prone to chronic malnutrition. The paper aims to analyze the magnitude and characteristics of food insecurity and nutrition vulnerability as well as to identify their causes. Thus, it is expected that the incident case management can be handled earlier. Periodically performing and updating food and nutrition insecurity mapping are very relevant. The level of food insecurity and malnutrition in Indonesia is almost high. In relation to the MDG target, conditions are still far from the targeted magnitude. It requires a breakthrough in reducing the prevalence of malnutrition among infants and energy deficit population. In addition, it needs sustainable food supply by increasing food production through food self-sufficiency. Thus, food and nutrition security approach is alternative to implement for handling food insecurity and malnutrition by increasing cross-sector synergy.